Developing a Regional Framework for Disaster Risk Reduction Based on Disaster-Related Data from Aceh, Indonesia - Yolanda, Yolanda; Oktari, Rina Suryani; Munawar, Munawar; Lola, Muhamad Safiih; Sofyan, Hizir (Heca Sentra Analitika, 2025)
Aceh Province is highly vulnerable to various hazards, necessitating effective disaster risk reduction strategies. This study aims to develop an instrument to evaluate disaster risk reduction efforts in Aceh Province and to assess progress toward global disaster resilience targets. The data includes secondary disaster-related records from 2005 to 2024 and primary data from the instrument validation process, demonstrating excellent validity results based on the Content Validity Ratio (CVR) and Content Validity Index (CVI). The findings highlight significant improvements in key areas, including reductions in disaster mortality, affected populations, economic losses, damage to critical infrastructure, and strengthened early warning systems. However, challenges persist in implementing local disaster risk reduction strategies and enhancing international cooperation. This study offers practical insights for policymakers and contributes to strengthening disaster resilience and advancing disaster risk management research in sub-national contexts.